2017
DOI: 10.1021/acs.chemmater.7b03555
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Ripening Mechanisms of Pd Clusters on Ceria

Abstract: We carried out density functional theory calculations to investigate the ripening of Pd clusters on CeO2(111). Starting from stable Pdn clusters (n = 1–21), we compared how these clusters can grow through Ostwald ripening and coalescence. As Pd atoms have mobility higher than that of Pdn clusters on the CeO2(111) surface, Ostwald ripening is predicted to be the dominant sintering mechanism. Particle coalescence is possible only for clusters with less than 5 Pd atoms. These ripening mechanisms are facilitated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(94 citation statements)
references
References 58 publications
9
85
0
Order By: Relevance
“…Pd, Au and Pt atoms prefer to be adsorbed on oxygen‐bridge site of CeO 2 (111),, while Cu atom preferentially locates on oxygen‐hollow site with a binding energy of 2.89 eV, in coincidence with the reported value of 3.03 eV . Figure shows the optimized configurations of isolated Cu atoms on various sites of CeO 2 (111).…”
Section: Figuresupporting
confidence: 67%
See 3 more Smart Citations
“…Pd, Au and Pt atoms prefer to be adsorbed on oxygen‐bridge site of CeO 2 (111),, while Cu atom preferentially locates on oxygen‐hollow site with a binding energy of 2.89 eV, in coincidence with the reported value of 3.03 eV . Figure shows the optimized configurations of isolated Cu atoms on various sites of CeO 2 (111).…”
Section: Figuresupporting
confidence: 67%
“…Single‐atom catalysts (SACs) abstract much attention due to the maximizing utilization of the precious metal components while offering the high reactivity and selectivity . However, metal single atoms generally have a high mobility and prefer to agglomerate into thermodynamically stable particles via Ostwald ripening . Therefore, the stability of the supported metal single atoms is vital for SACs.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In order to overcome the drawback associated with the conventional Pd/Al 2 O 3 catalysts, both theoretical and experimental investigations have suggested that the incorporation of ceria into Pd-based methane oxidation catalysts can result in improved catalytic activity and stability [21,[58][59][60]. For example Sheedeh and co-workers reported a comparative investigation of the activity of various Pd-based catalysts for application to methane oxidation.…”
Section: Catalytic Activitymentioning
confidence: 99%